Cell-specific immunohistochemical localization of a cellular retinol-binding protein (type two) in the small intestine of rat. - Crow, J A (1985)
One of us recently has reported the purification of a new retinol-binding protein that is distinctly different from the well-known cellular retinol-binding protein, CRBP. This protein, which we propose to name cellular retinol-binding protein type II [CRBP(II)], was found almost exclusively in the small intestine of the adult rat at levels 1000 times greater than that of CRBP. Here we have determined the cellular location of these two proteins in the small intestine of the rat. By using an immunohistochemical technique, the absorptive cells of the small intestine, from the duodenum to the ileum, were strongly stained when antiserum against CRBP(II) was used. More intense staining was observed in absorptive cells near the tips of the villi than in those located at the base of the villi. However, the proliferative cells in the crypts of Lieberkühn were stained only lightly if at all. In contrast to absorptive cells, goblet cells in the villi did not stain. When tissue sections containing the gastroduodenal junction were examined, no staining was observed in the gastric epithelium, while the epithelium of the most proximal portion of the duodenum showed very strong staining. In tissue sections containing the ileocecal junction, staining terminated abruptly at the end of the distal ileum. No staining was observed in the epithelium of the colon. In contrast, the cellular location of CRBP in the small intestine was quite different from the cellular location of CRBP(II). The epithelial cells of the small intestine showed no staining when affinity-purified anti-CRBP was used. Staining was observed for connective tissue cells in the lamina propria and in cells located within the gut-associated lymphoid tissue. The cell-specific localization pattern determined for these two proteins suggests that CRBP(II), rather than CRBP, is the protein that plays a role in the absorption of retinol.